Anodal transcranial direct current stimulation (atDCS) and functional transcranial Doppler sonography (fTCD) in healthy elderly and patients with MCI: modulation of age-related changes in word fluency and language lateralization - Heimann, Florian; Weiss, Sabine; Müller, Horst M. (Frontiers in Aging, 2024)
In addition to age-related changes in language, hemispheric lateralization of language functions steadily declines with age. Also, performance on word fluency tasks declines and is sensitive to the expression of dementia-related changes. The aim of this study is to evaluate the effect of anodal tDCS combined with a word fluency training on language lateralization and word fluency performance in healthy elderly subjects and in persons with mild cognitive impairment (MCI). The effect of anodal tDCS over the left inferior frontal gyrus (IFG) was measured in a group of healthy elderly up to the age of 67 years (YG, Ø = 63.9 ± 3.02), a group of healthy elderly aged 68 years and older (OG, Ø = 78.1, ± 4.85), and a group of patients with MCI (Ø = 81.18, ± 7.35) by comparing performance in phonological and semantic word fluency tasks before and after three days of tDCS. Half of the experimental participants received sham stimulation. In addition, language lateralization was determined using a lateralization index (LI) measured with functional transcranial Doppler sonography (fTCD) before and after the stimulation period. Anodal tDCS was associated with significantly higher scores in phonological but not semantic word fluency in both YG and OG. In MCI patients, no difference was measured between the tDCS and sham groups in either word fluency task. fTCD showed significantly increased left lateralization in all three groups after the training phase. However, this effect was independent of tDCS and the degree of lateralization could not be predicted by word fluency performance in any of the groups. Phonological word fluency can be increased with atDCS in healthy elderly people by stimulating the IFG in a three-day training. When cognitive decline has reached a certain stage, as is the case with MCI, this paradigm does not seem to be effective enough.